Is 40cmH(2)O detrusor leak point pressure cut-off reliable for upper urinary tract protection in children with myelodysplasia? - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TİNAY, İLKER; TARCAN, TUFAN; TANIDIR, YILÖREN (WILEY, 2017)
PurposeThe purpose of this study, is to find out the most accurate cut-off level for the detrusor leak point pressure (DLPP) in terms of upper urinary tract (UUT) protection in a cohort of children with myelodysplasia. Materials and MethodsOne hundred and ninety-three children with myelodysplasia were included in the study based on the availability of urological evaluation at age of 3 years. Children were assigned to one of two groupsthose who had UUT damage at age 3 (group 1, n: 70) and those without UUT changes (group 2, n: 123), and compared. ResultsUrological follow-up data revealed higher incidences of febrile urinary tract infections and secondary tethering of the spinal cord in group 1. No statistically significant difference was determined between group 1 and group 2 in terms of DLPP values (median 42.5 vs. 39.5cmH(2)O, respectively, P=0.087). Analysis of different cut-off values showed that DLPP above 20cmH(2)O had a higher sensitivity for UUT damage (91.4%). A normal UUT was found in 56.5% and 62.2% of children with DLPP between 20 and 40cmH(2)O, and with DLPP over 40cmH(2)O, respectively. ConclusionsPresent study showed that more than half of the children with myelodysplasia had normal UUT function even with a DLPP of 40cmH(2)O and over. Thus, DLPP, is not the sole decision making parameter to rely for more invasive therapies in children with myelodysplasia. On the other hand, a DLPP cut-off value of 20cmH(2)O showed a higher sensitivity to predict UUT damage instead of 40cmH(2)O. Neurourol. Urodynam. 36:759-763, 2017. (c) 2016 Wiley Periodicals, Inc.
Keywords: detrusor leak point pressure; myelodysplasia; neurogenic bladder; upper urinary tract deterioration; NEUROGENIC BLADDER; SPINA-BIFIDA; RISK-FACTORS; MYELOMENINGOCELE; MENINGOMYELOCELE; PERFORMANCE; DYSFUNCTION; NEWBORNS; REFLUX